Fake News: Is it Made for Men or Women? - Galyna Tsapro; Олена Грищенко (Філологічні студії, 2023)
Fake news has become an integral part of modern life. It represents a distinct genre within news discourse, characterized by manipulation and the dissemination of deceptive information through mass media. Fake news is primarily defined by elements of 'falsehood,' 'deceit,' and 'manipulation,' which underlie its close connection with both misinformation and disinformation. Those who create fake news often tailor their content to exploit the potential interests and vulnerabilities of their target audience, including gender-related themes and stereotypes to generate heightened engagement.